Developing Learning Media Based on Geographic Information System for Geography Subject in Senior High Schools - Arrasyid, Riko; Setiawan, Iwan; Sugandi, Dede (Universitas Pendidikan Indonesia, 2019)
This study aims to develop learning media based on Geographic Information Systems (GIS) in Geography subject in high schools. This research was designed to develop space-based geography learning media with various data formats (multimedia) and interface design easy to operate. This study uses a quasi-experimental design to examine whether there is an influence of the use of GIS in geography learning. The subjects of the study were social class elevnth graders at SMAN 15 Kota Bandung, Indonesia which is the experimental site as well. On class (social class 2) was selected to an experimental group and the other class (social class 4) served as a control group. The instrument used is a multiple choice test. The analytical technique used is Kolalogov-Smirnov. Based on the results of the analysis and discussion, it can be concluded that the development of GIS-based geography learning media can be developed as a geography learning media by designing an easy and simple application interface to be used by teachers and students as well as databases that are in accordance with the curriculum. GIS-based learning media developed showed significant influence on learning achievement of learners. The experimental class performed higher learning achievement than the control class.